2014
DOI: 10.1128/jvi.00936-14
|View full text |Cite
|
Sign up to set email alerts
|

Late Endosomal Trafficking of Alternative Serotype Adenovirus Vaccine Vectors Augments Antiviral Innate Immunity

Abstract: Adenovirus (Ad) vaccine vectors have found widespread use as vaccine platforms against multiple infections and cancers, and multiple serotypes have been shown to differ significantly in their biological properties and immune phenotypes. Our laboratory and others have previously described differential innate immune stimulation elicited by various Ad serotypes. Here, we show that Ad serotype 5 (Ad5) traffics rapidly to the nucleus following infection, whereas Ad35 and Ad26 accumulate in late endosomes 2 to 8 h p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…Thus, differences in capsid stability may be the primary determinant of entry-associated sorting for all AdVs, allowing endosomal escape in very early endocytic compartments (as observed for species C AdVs) or after prolonged sorting from the late endosomal/lysosomal compartment, as was suggested for species B viruses (28,63). In contrast, premature protein VI release (e.g., PVI-L40Q) or failure to release protein VI at all (PRO-P137L) would result in noninfectious virions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, differences in capsid stability may be the primary determinant of entry-associated sorting for all AdVs, allowing endosomal escape in very early endocytic compartments (as observed for species C AdVs) or after prolonged sorting from the late endosomal/lysosomal compartment, as was suggested for species B viruses (28,63). In contrast, premature protein VI release (e.g., PVI-L40Q) or failure to release protein VI at all (PRO-P137L) would result in noninfectious virions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, differences in antiviral innate immune activation may have consequences for vaccine strategies when vectors are based on different viral backbones. Recent reports identified serotype-specific innate immune responses in the in vivo murine model (16). Suggestions that differences in immune potency correlate with genome sequence have been made (42).…”
Section: Discussionmentioning
confidence: 99%
“…Most Ads bind to the coxsackievirus-adenovirus receptor (CAR) (12), but CD46 is the high-affinity receptor targeted by subgroup 1 species B viruses (13), and desmoglein-2 binds fiber of the subgroup 2 species B viruses (14). Recent studies have indicated that differences in fiber/receptor binding influence the viral endocytic import pathway (15) and antiviral activation levels (16).…”
mentioning
confidence: 99%
“…IL-12 levels in samples obtained 6 hours after administration of AdDRGD were three times lower than those from mice given AdlacZ (392.1 6 26.1 pg/ml); however, the concentration of this cytokine was significantly higher than that detected in the AdlacZ group at the 24-hour (247.6 6 30.3 pg/ml) and 48-hour (270.0 6 18.6 pg/ml) time points. This finding was somewhat unexpected; however, early studies with AdDRGD and the native wild-type virus described notable differences in intracellular trafficking and endosomal escape patterns (Shayakhmetov et al, 2005a), processes that significantly affect development of the innate immune response to the virus (Leopold and Crystal, 2007;Teigler et al, 2014). Other studies in which AdDRGD was given to mice in the same manner as described in our studies have reported notable suppression of a variety of proinflammatory cytokines (Di Paolo et al, 2009); however, levels of cytokines with dual inflammatory and protective roles after administration of the virus have not previously been described.…”
Section: Integrins and Drug Metabolismmentioning
confidence: 87%